Transcranial Doppler in a child: A most valuable imaging modality. (May 2022) - Deana, Cristian; Vetrugno, Luigi; Stefani, Francesca; Bassi, Flavio; Bove, Tiziana
Introduction: Pediatric brain injury is a common cause of emergency department (ED) referral. Although severe traumatic brain damage is less frequent, it could be primarily managed by non-pediatric critical care physicians called in for advice. Clinical evaluation is important, but radiology is of particular value in the case of severe brain injury. Transcranial Doppler may help the physician through neuromonitoring. Case Report: We report the case of a 3-year-old male child brought into the pediatric ED for a moderate head injury. His neurological status deteriorated rapidly, making endotracheal intubation and mechanical ventilation necessary. Computed tomography (CT) of the head revealed brain contusion and post-traumatic subarachnoidal hemorrhage. Discussion: Transcranial Doppler was performed at the standard transtemporal evaluation window, and it showed normal vascularization of the entire anterior brain. This result permitted performance of the control CT scan to be postponed. In this case, basic knowledge of transcranial ultrasound proved to be useful, and we believe it could also be useful to other colleagues faced with similar situations even if they are not dedicated to pediatric critically ill patients. Conclusion: Doppler ultrasound in the pediatric population is a valuable bedside tool. Together with clinical evaluation and radiology, it completes the set of techniques necessary for continuous neuromonitoring.